Rancang Bangun Dashboard Sistem Informasi Logistik untuk Monitoring Kinerja Pengiriman dan Analisis Produktivitas Keuangan - Muhammad Aliep; Muhammad Ersyad Baidilah; Umar Muhtar; Ines Heidiani Ikasari; Arya Septa Wicaksana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of information technology has increased the need for logistics companies to manage operational and financial information in an integrated, timely, and accurate manner. PT. Arya Mandiri Translogistik previously managed customer, order, shipment, and operational expense data through separate media, creating delays in monitoring and increasing the risk of inconsistent records. This study aims to design and implement a web-based Logistics Information System Dashboard that integrates shipment performance monitoring and financial productivity information within a centralized platform. System development employed the Waterfall method through requirement analysis, system design, implementation, testing, and maintenance stages. The application was developed using PHP and MySQL, while system interactions and database relationships were modeled using Use Case Diagrams, Activity Diagrams, and an Entity Relationship Diagram. The implemented dashboard provides multi-user authentication, customer and product management, order and shipment tracking, operational expense recording, financial summaries, and integrated information displays. Functional validation was conducted through Black Box Testing on authentication, customer management, shipment monitoring, and financial report modules. The results show that all tested scenarios produced outputs consistent with the specified functional requirements and were categorized as valid. The dashboard centralizes operational data, facilitates shipment status monitoring, supports faster report preparation, and provides management with more structured information for decision-making. Further development is required for automated notifications, interactive key performance indicators, real-time tracking integration, security testing, and performance evaluation.